2018
DOI: 10.3390/en11082118
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Adaptive Filtering-Based Energy Management Strategy for Fuel Cell Hybrid Electric Vehicles

Abstract: The global need to solve pollution problems has conducted automotive engineers to promote the development and the use of electric vehicle technologies. This paper focuses on the fuel cell hybrid electric vehicle which uses a proton exchange membrane fuel cell as a main source associated to hybrid storage device: lithium ion battery and ultracapacitors. A common interest in such technology is to spread out the energy flow between its different sources in order to satisfy the power demand for any requested missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 42 publications
0
45
0
1
Order By: Relevance
“…The SOC of the SC ( ) is defined as the ratio of the voltage of the SC ( ) to its maximum voltage of SC ( _ ). The is calculated using [37]: Table 1 presents the main parameters of the SC model used in this paper.…”
Section: Supercapacitor Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…The SOC of the SC ( ) is defined as the ratio of the voltage of the SC ( ) to its maximum voltage of SC ( _ ). The is calculated using [37]: Table 1 presents the main parameters of the SC model used in this paper.…”
Section: Supercapacitor Modelingmentioning
confidence: 99%
“…The SOC of the SC (SOC sc ) is defined as the ratio of the voltage of the SC (V sc ) to its maximum voltage of SC (V sc_max ). The SOC sc is calculated using [37]: The battery is the main ESS for an EV, which is connected directly to a DC bus in a semi-active HESS. The charging and discharging of the battery considerably depends on various parameters, such as temperature (T) and the SOC of the battery (SOC bat ) [35].…”
Section: Battery Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some interesting research works that have been carried out with the combination of the battery and SCs or the battery and HC with renewable energy sources such as photovoltaic (PV) systems, fuel cells, and wind turbines. Some of these studies can be found in [30][31][32][33][34][35][36]. The dearth of research involving the use of LiCs cannot be overemphasized, particularly in energy storage hybridisation.…”
Section: Introductionmentioning
confidence: 99%